2017
DOI: 10.1093/ejcts/ezx395
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of annuloplasty in trivial-to-mild functional tricuspid regurgitation during mitral valve replacement: should we perform annuloplasty on the tricuspid valve or leave it alone?

Abstract: Patients with untreated trivial or mild functional TR accompanied by mitral valve disease can develop significant TR during follow-up. TV ring annuloplasty can be performed without complications and can be beneficial for patients with trivial or mild functional TR who are undergoing MVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
7
27
1
Order By: Relevance
“…However, Dhoble et al [18], in a study on 6,868 patients who had TV surgery, found that concomitant TV surgery was associated with higher mortality, complications, and length of stay than isolated MV surgery. Meanwhile, in other series, concomitant repair of functional TR during MV surgery did not increase the operative risk and was associated with favourable long-term outcomes [3,19].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, Dhoble et al [18], in a study on 6,868 patients who had TV surgery, found that concomitant TV surgery was associated with higher mortality, complications, and length of stay than isolated MV surgery. Meanwhile, in other series, concomitant repair of functional TR during MV surgery did not increase the operative risk and was associated with favourable long-term outcomes [3,19].…”
Section: Discussionmentioning
confidence: 80%
“…Recent guidelines for management of functional tricuspid regurgitation (TR) during left sided valve surgery recommend tricuspid valve annuloplasty in severe TR (class I), or even in the presence of moderate functional TR if the diameter of the tricuspid annulus is .40 mm or in patients with progressive right ventricular dysfunction (class IIa) [1,2]. Reports on the management of mild and moderate secondary TR are controversial [3], and recent studies doubt the value of concomitant tricuspid valve (TV) repair during mitral valve (MV) surgery because progression to severe TR is uncommon [4].…”
Section: Introductionmentioning
confidence: 99%
“…Annular dilatation was diagnosed when the annulus was larger than the ring sizer matching the intercommissural distance of the septal leaflet. 13 According to the surgeon's preference, not all patients who met the indications underwent TAP. The size of the ring was based on the intercommissural distance of the septal leaflet and the area of the leaflet attached to the chordae originating from the anterior papillary muscle.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…7 Recently, Choi et al saw similar results in their 2004 to 2014 population, showing that TR annuloplasty is low risk and reduces the rates of late TR following MV surgery. 8 These findings lead to the conclusion that the TV will not "fix itself" and would require other approaches. Comparisons between the suture annuloplasty (De Vega procedure and modified De Vega procedure) and ring annuloplasty demonstrate that suture annuloplasty did not have long-term durability and was inferior to ring annuloplasty in preventing late recurrence of TR.…”
mentioning
confidence: 99%
“…16 Choi et al examined long-term outcomes of patients with trivial or mild TR at the time of mitral surgery and found increased freedom from late TR at 5 and 10 years for those who underwent prophylactic TV repair (p = 0.013, p = 0.047, respectively). 8 More than just ubiquitous application of annuloplasty to dilated TV annulus, the ability to predict failure of repair and direct the surgical decision-making toward replacement further reflects the maturation of TV surgery. It is well understood that the left ventricular ejection fraction can be falsely reassuring in the setting of severe mitral regurgitation.…”
mentioning
confidence: 99%